The Use of Picture Series to Improve Students Speaking Ability at Eight Grade of SMP Negeri Weet MBD - Knyartutu, Marthin Novel; Ferdinandus, Mercy; Tiwery, Yulina (Koli Journal : English Language Education, 2023)
The purpose of this research was to know whether the use of picture series can improve students’ speaking ability in English learning. This classroom action research was done in SMP NEGERI WEET MBD. The result of this research showed that picture series had positive role in improving the speaking ability at the eight grade of the students . The average score from pre-test was 40,90 and in post-test 68.19 became 77. 28. It means that the use of picture series in speaking skill can improve the students’ speaking skill. The students were actively engaged in teaching learning process. It made the students easy to understand the material so it facilitated students’ speaking mastery. This could be seen from the result obtained after execution of action on cycle 1 in which 68.19 % of the students reached minimum criterion for success (KKM). Then performance on cycle 2 increased to 77. 28 % where this amount of students had reached KKM.